State diagrams for improving processing and storage of foods, biological materials, and pharmaceuticals (IUPAC Technical Report) - Buera, Maria del Pilar (2011)
Supplemented temperature/composition phase diagrams include the non-equilibrium glass-transition temperature (Tg) curve and equilibrium ice-melting and solubility curves. The inclusion of the non-equilibrium curve allows one to establish relationships with the time coordinate and, thus, with the dynamic behavior of systems, provided that the thermal history of such systems is known. The objective of this report is to contribute to the potential applications of supplemented state diagrams for aqueous glass-formers, in order to describe the influence of water content, nature of vitrifying agents, and temperature on the physico-chemical properties of foods and biological and pharmaceutical products. These data are helpful to develop formulations, processing strategies, or storage procedures in order to optimize the stability of food ingredients and pharmaceutical formulations. Reported experimental data on phase and state transitions for several food and pharmaceutical systems were analyzed. Some methodological aspects and the effect of phase and state transitions on the main potential chemical reactions that can alter those systems during processing and/or storage are discussed.